Modeling and ARX identification of a quadrotor MiniUAV - Sarioglu, Atakan; Kural, Ayhan (IEEE, 2015)
In this work, a miniature-sized, radio controlled quadrotor is modeled and a black-box model is found using real-time flight data. The quadrotor which is used in this work is equipped with a special telemetry circuit to collect real-time data. Euler angles versus motor speeds data is used to identify the nonlinear rotational subsystem of the quadrotor as a quasi-linear ARX (auto-regressive exogenous) model. The ARX model performances are tested and found quite satisfactory.